Relation Helicobacter pylori with Pathogenesis of Stomach and Immune Responses - Hussein Al–Mousawi, Alia; Hussein Neamah, Bent alhuda; Mohammed Chessab, Roaa; Haider Aldujaili , Hadeel; Mohammed Chessab, Jannat (Medical Science Journal for Advance Research, 2022)
Background: Helicobacter pylori, a member of Epsilonproteobacteria, is a Gram-negative microaerophilic bacterium that colonizes gastric mucosa of about 50% of the human population. Although most infections caused by H. pylori are asymptomatic, the microorganism is strongly associated with serious diseases of the upper gastrointestinal tract such as chronic gastritis, peptic ulcer, duodenal ulcer, and gastric cancer, and it is classified as a group I carcinogen. The prevalence of H. pylori infections varies worldwide. prevalence among middle-aged adults is over 80 percent in many developing countries, as compared with 20 to 50 percent in industrialized countries. The infection is acquired by oral ingestion of the bacterium and is mainly transmitted within families in early childhood, Humans can also become infected with Helicobacter heilmannii, a spiral bacterium found in dogs, cats, pigs, and nonhuman primates. Conclusion: H. pylori infection stimulates the reaction of autoantibodies with gastric epithelial cells, and this leads to gastritis. These autoantibodies can be directly induced to epithelial cells by activating complement, inducing apoptosis or provoking an antibody-dependent cytotoxic reaction resulting in subsequent tissue destruction.